Cancer/testis antigens: promising immunotherapy targets for digestive tract cancers - Ai, Huihan; Yang, Hang; Li, Liang; Ma, Jie; Liu, Kangdong; Li, Zhi (Frontiers in Immunology, 2023)
Digestive tract cancers, including esophageal, gastric, and colorectal cancers, are the major cause of death among cancer patients worldwide due to the heterogeneity of cancer cells, which limits the effectiveness of traditional treatment methods. Immunotherapy represents a promising treatment strategy for improving the prognosis of patients with digestive tract cancers. However, the clinical application of this approach is limited by the absence of optimal targets. Cancer/testis antigens are characterized by low or absent expression in normal tissues, but high expression in tumor tissues, making them an attractive target for antitumor immunotherapy. Recent preclinical trials have shown promising results for cancer/testis antigen-targeted immunotherapy in digestive cancer. However, practical problems and difficulties in clinical application remain. This review presents a comprehensive analysis of cancer/testis antigens in digestive tract cancers, covering their expression, function, and potential as an immunotherapy target. Additionally, the current state of cancer/testis antigens in digestive tract cancer immunotherapy is discussed, and we predict that these antigens hold great promise as an avenue for breakthroughs in the treatment of digestive tract cancers.